THE LANGUAGE INSTINCT (Steven Pinker vs Noam Chomsky) - Nur Cahaya Sihombing (Journal of Applied Linguistics, 2022)
Language is a communication tool used in daily interaction. Language used to convey meaning to someone with easy word order understandable. Therefore, in order to convey the meaning clearly, use of the correct language is very important. This paper examines Steve Pinker’s arguments for the existence of a language instinct encoded in the genes of human beings as an explanation for the human language capacity. The analysis covers Pinker’s own arguments as well as those by Chomsky and by other authors in the 1990s. Argumen of Steven Pinker language is first and foremost a product of our biological make-up as a species. Pinker does not mean to deny the influence of culture on language, but means that language grows out of the "predisposition" or biological readiness of every normal human being. Human infants have a natural gift for quickly absorbing and then using the structures of spoken language used by others around them. According to Chomsky, children are born with the tools of acquisition Language. " language acquisition device (LAD). This tool is a biological gift that has been programmed to detail the possible items of a grammar. LAD is considered to be a specialized physiological part of the brain to process language. So it can be seen that experts have given the same theory and opinion regarding the way of language development and acquisition, which is related to the language instinct that has existed since in the womb. Key Word : The Language Instinct